Piles Subjected to Torsional Cyclic Load: Numerical Analysis - Nimbalkar, Sanjay Shrawan; Punetha, Piyush; Basack, Sudip; Mirzababaei, Mehdi (Frontiers in Built Environment, 2019)
Pile foundations supporting large structures (such as high-rise buildings, oil drilling platforms, bridges etc.) are often subjected to eccentric lateral load (in addition to the vertical loads) due to the action of wind, waves, high speed traffic and ship impacts etc. The eccentric lateral load, which is usually cyclic (repetitive) in nature, induces torsion in the pile foundation. This paper presents a numerical model based on boundary element approach to study the performance of a single pile subjected to the torsional cyclic load. The model is initially validated by comparing it with the experimental data available from the literature. Thereafter, the model has been utilised to conduct a parametric study to understand the influence of the torsional cyclic loading parameters on the axial pile capacity. The results indicated that the model is able to capture the degradation in the axial pile capacity due to the torsional cyclic loading with a reasonable accuracy. Moreover, the parametric study showed that the frequency, amplitude and number of cycles play a significant role in the torsional cyclic response of the pile. The present study is essential for the development of design guidelines for pile foundations subjected to torsional cyclic load.